Discussion of the special issue. Beliefs about multilingualism: is a methodological and epistemological change necessary?. Issue 1 (2nd January 2023) - Chik, Alice; Melo-Pfeifer, Sílvia
ABSTRACT: In this commentary to the special issue, we will present our personal understanding of how its five papers contribute to advance the research field of beliefs about multilingualism and a critical stance on how multilingualism has been approached in the literature. We will point some ways forward on the research on beliefs about multilingualism claiming that this research area needs to shift from a rather Eurocentric perspective, to embrace less logocentric research methods, and to critically examine its stance on multilingualism, by considering intersectionality on the ways beliefs are studied.